Assessment of depression in patients with open-angle glaucoma - Cvetković, Aleksandra; Srećković, Sunčica; Paunović, Svetlana (Vojnosanitetski pregled, 2024)
Background/Aim. Depression can be caused by a life situation. The aim of the study was to determine the influence of glaucomatous damage on the frequency of occurrence of depression, as well as to determine the risk factors for the onset of depression in patients with open-angle glaucoma (OAG). Methods. The study was designed as a clinical, observational study (cross-sectional study). The research included 150 patients of both genders over the age of 40 with a confirmed diagnosis of OAG. Anamnestic and sociodemographic data were collected by a questionnaire and detailed ophthalmological examinations were performed. The Beck Depression Inventory-II scale was used as a measurement instrument to assess depression. Results. A high (51.3%) prevalence of depressive symptoms in patients with OAG was confirmed. The patients who suffered from depression more often were women, people with lower monthly earnings, and lower mean deviation values of the visual field index. In patients with advanced glaucoma, a significantly higher frequency of depressive symptoms was observed. Conclusion. Due to the high prevalence of depressive symptoms, it is important to introduce a multidisciplinary approach to treatment by ophthalmologists and psychiatrists. Detecting and treating depressive symptoms at an early stage of the disease leads to a significant reduction in treatment costs and patient disability.
Keywords: age factors; depression; glaucoma, open-angle; socioeconomic factors; risk factors; surveys and questionnaires